Antibiotic prophylaxis for premature rupture of membranes and perinatal outcome. (4th March 2017) - Barišić, Tatjana; Mandić, Vjekoslav; Tomić, Vajdana; Zovko, Ana; Novaković, Gorjana
Abstract: Aim : To evaluate the perinatal outcomes of newborns after premature rupture of membranes (PROM) at the term according to the timing of initial antibiotic administration. Material and methods : This is a retrospective, cohort study investigating perinatal outcomes of newborns in pregnant women with PROM at the term who were treated with ampicillin within or after 6 h from the PROM. Statistical analysis was performed using Student's t -test for continuous variables test and chi-square or for categorical data. Results : The study involved 144 pregnant women with PROM and their newborns, a lower number received antibiotics after birth were in the group who received antibiotics within 6 h of PROM (26.4% versus 73.6%), the mediane values of C-reactive protein were lower (3.0 ± 2.9 mg/l versus 6.1 ± 7.3 mg/l; p < 0.001), their newborns remained shorter in hospital after birth (4.13 versus 4.94; p =0.023) and time between PROM and delivery was shorter ( p < 0.001). In group who received prophylactic antibiotics after 6 h of the PROM had significantly higher frequency of infection in newborns (45.3% versus 15.4%), and higher number of chorioamnionitis (9.72% versus 3, 47%) compared to group who received antibiotics within 6h. Conclusion : Timely usage of antibiotic prophylaxis and shorter time between PROM and delivery improve perinatal outcomes.